2000
DOI: 10.1002/(sici)1097-0347(200005)22:3<297::aid-hed14>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Cancer of the tongue in patients less than forty

Abstract: Introduction It is the opinion of many surgeons that the biologic potential of cancer that develops in young people is different compared with older patients. Prior reports on small series of patients addressing this issue have inadequate statistical power to resolve the question. Methods By use of the techniques of meta‐analysis, patients less than 40 years old who had undergone treatment of squamous cell carcinoma (SCC) of the oral tongue were examined. Twenty‐eight patients who were encountered in the Depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
77
4
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 34 publications
13
77
4
3
Order By: Relevance
“…Recently, there has been an increase in the number of young adults who develop oral cancer especially cancer of the tongue, without any apparent risk factors such as tobacco use or immunosuppressant (Llewellyn et al, 2001;Pitman et al, 2000).…”
Section: Demographic Features Of People With Oral Cancermentioning
confidence: 99%
“…Recently, there has been an increase in the number of young adults who develop oral cancer especially cancer of the tongue, without any apparent risk factors such as tobacco use or immunosuppressant (Llewellyn et al, 2001;Pitman et al, 2000).…”
Section: Demographic Features Of People With Oral Cancermentioning
confidence: 99%
“…Other aspects of the disease also differ between young and old patients, for example the male to female ratio is lower in the younger group (11). SCCHN has been described in some reports as being more aggressive in younger patients (12,13), whereas other reports have not found any difference, or even seen better survival in young patients (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…It seems that biological behavior and etiology of OSCC in young patients are unlike older age groups and some studies suggest that oral cancer in young patients is more aggressive (6). Recent studies revealed that there is no difference between clinical course and survival rate (2,(7)(8)(9). Iran is a large country located in the Middle East and Khorasan is one of the largest provinces in Iran covering 7.8% of the total area of this country.…”
Section: Introductionmentioning
confidence: 99%